2000
DOI: 10.1080/15216540050212088
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8 in Apoptosis: The Beginning of "The End"?

Abstract: Caspase-8 is a member of the cysteine proteases, which are implicated in apoptosis and cytokine processing. Like all caspases, caspase-8 is synthesized as an inactive single polypeptide chain zymogen procaspase and is activated by proteolytic cleavage, through either autoactivation after recruitment into a multimeric complex or trans-cleavage by other caspases. Thus, ligand binding-induced trimerization of death receptors results in recruitment of the receptor-specific adapter protein Fas-associated death doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(121 citation statements)
references
References 0 publications
4
116
0
1
Order By: Relevance
“…Caspase-8 is an initiator caspase to cleave inactive pro-forms of effector caspases, thereby activating them to trigger apoptosis (22). It is activated in response to agents or insults inducing the release of cytochrome from the inner mitochondrial membrane (23), playing a crucial role in generating cell apoptosis downstream pathway (24). Caspase-3 is required for cell deaths and distinct apoptotic processes (25).…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-8 is an initiator caspase to cleave inactive pro-forms of effector caspases, thereby activating them to trigger apoptosis (22). It is activated in response to agents or insults inducing the release of cytochrome from the inner mitochondrial membrane (23), playing a crucial role in generating cell apoptosis downstream pathway (24). Caspase-3 is required for cell deaths and distinct apoptotic processes (25).…”
Section: Discussionmentioning
confidence: 99%
“…We proceeded to determine the levels of some of the other components of the ''death ligand'' apoptotic pathway by Western blot, specifically caspase-8, an initiator caspase of the Fas signaling pathway 48,49 and c-FLIP isoforms. Both large and small c-FLIP can form inactive heterodimers with caspase-8 (FLICE), and thus act as apoptosis inhibitors early in the pathway.…”
Section: Death Ligand Gene Therapy Of Brain Tumor Cells S Rubinchik Ementioning
confidence: 99%
“…By associating with the adaptor molecules such as Fas-associating protein with death domain (FADD), activated receptors recruit procaspase-8 to the receptor complex, where it undergoes autocatalytic activation. 6,17 In contrast to the physiological machinery, artificial approaches of initiator caspase activation have been developed. [8][9][10][11][12] In principle, the target caspase is fused to a heterologous domain which dimerizes either spontaneously or upon induction by a small dimeric ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the active caspase-8 initiates a protease cascade and causes the activation of another group of caspases, effector caspases, ultimately leading to the irreversible cleavage of target proteins and apoptotic cell death. 3,6,7 An "induced proximity model" of caspase activation has been established by different researchers since 1998, which demonstrated that caspase-8 could be activated after an inducible dimerization driven by a heterologous domain fused to the zymogen. [8][9][10][11][12] Breast cancers are among the most threatening malignancies and are responsible for about 20% of women's deaths worldwide.…”
Section: Estrogen-induced Dimerization and Activation Of Erα-fused Camentioning
confidence: 99%
See 1 more Smart Citation